Atributos físicos do solo em diferentes condições de cobertura vegetal em área de plantio direto - De Rossetti, Karina V. [UNESP]; Andrioli, Itamar [UNESP]; Centurion, José F. [UNESP]; Matias, Sammy S. R.; Nóbrega, Júlio C. A. (Revista Brasileira de Ciencias Agrarias, 2012)
The use of cover crops in the soil causes changes in soil attributes influencing in a series of hydro-physical processes, which also modify the ability of soil to support the many activities that it is intended. Thus, the objective of this study was to evaluate the effect of cover crops on physical attributes of the soil. For this, an experiment was carried out on a Typic Hapludox, Jaboticabal State, Brazil, using cover crops of millet, sunn hemp, jack bean, lab-lab and black velvet bean in no-tillage and fallow area (spontaneous vegetation). The characteristics evaluated were the bulk density, macroporosity, microporosity, total porosity, aggregate stability, penetration resistance and organic matter. The incorporation of cover crops has proved to be a beneficial practice for the physical attributes of the soil, allowing a greater aggregate stability compared to fallow in the depth of 0-0.05 m. All cover crops presented values of soil penetration resistance below the critical value of 2 MPa.
Soil physical attributes under different cover crops in an area of no-tillage
Keywords: Compact; Conservationist management; Green manure; Canavalia ensiformis; Cannabis; Crotalaria juncea; Mucuna